Nigerian Feminism: A Typology of African Feminism - Olatokun, Ganiat M. (NIU Journal of Humanities; Vol 2 No 1 (2017): KIU Journal of Humanities, Vol. 2 No. 1, June 2017, 2017)
Severally, European and North American feminists have often been blamed for imposing the historical and cultural experiences of North America and Europe on African women, and Nigerian women in particular. It is a fact as well as a truism that African and Western societies have different historical antecedents. Historical differences like colonialism and neo-colonialism have grave effects and consequences for the role, position and status of women. Like women all over the world, African women haveobstacles and challenges and they are the only one who can set right their priorities and agendas. It is in this vein that, the author carried out a case study in eight different states in Nigeria asking question relating to feminism awareness in Nigeria. The result shows that, all the participants had some ideas of what is meant by feminism. In all their responses, the sensitivity of their positions culturally and traditionally was a re-echoed stance. Hence, the author, going in line with Catherine Acholonuâ€™s Motherism, Obioma Nmaemekaâ€™s Negofeminism and Chikwenye Okonjo-Ogunyemiâ€™s African Womanism has coined out what she termed, â€œNaijafeminismâ€ (an acronym for Nigerian feminism), a paradigm and movement which is shaped by Nigerian contexts and experiences. Keywords: Nigeria, Feminism, Women, Tradition, Motherhood